A topographically controlled tipping point for complete Greenland ice sheet melt - M. Petrini; M. Petrini; M. D. W. Scherrenberg; L. Muntjewerf; L. Muntjewerf; M. Vizcaino; R. Sellevold; G. R. Leguy; W. H. Lipscomb; H. Goelzer (The Cryosphere)
A major impact of anthropogenic climate change is the crossing of tipping points, which may have severe consequences such as the complete mass loss of the Greenland ice sheet (GrIS). At present, the GrIS is losing mass at an accelerated rate, largely due to a steep decrease in its surface mass balance (SMB; the balance between snow accumulation and surface ablation from melt and associated runoff). Previous work on the magnitude and nature of a threshold for GrIS complete melt remains controversial. Here, we explore a potential SMB threshold for complete melt of the GrIS; the impact and interplay of surface melt and glacial isostatic adjustment (GIA) in determining this threshold; and whether the GrIS exhibits characteristics commonly associated with tipping points, such as sensitivity to external forcing. To this end, we force the Community Ice Sheet Model v.2 (CISM2) by cycling different SMB climatologies previously calculated at multiple elevation classes with the Community Earth System Model v.2 (CESM2) in a two-way coupled CESM2–CISM2 transient simulation of the global climate and GrIS under high CO2 forcing. The SMB calculation in CESM2 has been evaluated with contemporary observations and high-resolution modelling and includes an advanced representation of surface melt and snow–firn processes.